Analisis Efektivitas Coretax dalam Meningkatkan Penerimaan Pajak Negara: Studi Kasus pada Direktorat Jenderal Pajak - Sintania Apriliani; Stevina Marcellia; Riska Melani Agustina; Amalia Solehah; Nurlita Widya Ningrum (AKUNTANSI 45, 2025)
This study aims to analyze the effectiveness of the implementation of the Core Tax Administration System (CTAS) in improving Indonesia’s national tax revenue, using a case study of the Directorate General of Taxes (DGT). Coretax is part of the third phase of tax reform focusing on the modernization of tax administration through digitalization and integrated data management. This research employs a descriptive quantitative approach using secondary data obtained from the Directorate General of Taxes (DGT) annual reports and the State Budget (APBN) realization reports for the 2023-2025 period. The analysis was conducted by calculating the effectiveness ratio between the target and the realization of tax revenues for each year. The results indicate that before the implementation of Coretax (2023-2024), the effectiveness level of tax revenue was categorized as very effective, with ratios exceeding 100%. However in 2025 the initial period of Coretax implementation, the effectiveness decreased to 39.56% due to adaptation processes, data migration, and system adjustments. Despite this decline, the change represents a transitional phase toward a more efficient, transparent, and integrated tax administration system. Therefore, the implementation of Coretax is projected to strengthen tax governance and enhance national tax revenue in the long term.